Elm forests in North Bulgaria and conservation strategies - Stoyanov, N.
(Es, En)
ilus.,8 ref.
Keywords: ULMUS; VARIACION GENETICA; MEJORA GENETICA; RECURSOS GENETICOS; ESPAÑA; INVENTARIO GENETICO; OLMO